2020
DOI: 10.3389/fonc.2020.545078
|View full text |Cite
|
Sign up to set email alerts
|

Competing Risks of Cancer and Non-Cancer Mortality When Accompanied by Lifestyle-Related Factors—A Prospective Cohort Study in Middle-Aged and Older Adults

Abstract: BackgroundThe study aimed to identify the association between the lifestyle-related factors and the cancer-specific, or non-cancer-specific mortality, when accompanied by a competing risk. Two statistical methods were applied, i.e., cause-specific hazard (CSH), and sub-distribution hazard ratio (SHR). Their respective key advantages, relative to the actual study design, were addressed, as was overall application potential.MethodsSource data from 4,584 residents (34.2% men), aged 45–64 years, were processed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The measurements of waist and hip circumferences were taken using a metric, nonelastic measuring tape, positioned parallel to the floor and recorded to an accuracy of 0.1 cm, in line with anthropometric measurement guidelines [24][25][26]. In accordance with the WHO protocols, WC was measured at the midpoint between the iliac crest and the lower border of the last palpable rib, in the mid-axillary line.…”
Section: Adipose Tissue Distribution Measurementsmentioning
confidence: 99%
“…The measurements of waist and hip circumferences were taken using a metric, nonelastic measuring tape, positioned parallel to the floor and recorded to an accuracy of 0.1 cm, in line with anthropometric measurement guidelines [24][25][26]. In accordance with the WHO protocols, WC was measured at the midpoint between the iliac crest and the lower border of the last palpable rib, in the mid-axillary line.…”
Section: Adipose Tissue Distribution Measurementsmentioning
confidence: 99%
“…Deaths of lung cancer patients are caused by various risk factors, the main one being smoking [7][8][9][10][11][12]. A large Norwegian study found that men who smoke had a 27-fold higher risk of death [12].…”
Section: Introductionmentioning
confidence: 99%
“…A large Norwegian study found that men who smoke had a 27-fold higher risk of death [12]. Other characteristics related to the mortality of lung cancer are sex (men have a higher risk than women) [7,12], age (a higher risk with increasing age) [7,10,11], body mass index (being overweight is riskier) [13,14], family history [8,10], and cancer stage [7,15]. Furthermore, external factors such as air pollution can have a significant effect on mortality; for example, PM (both PM ≤ 2.5 µm (PM2.5) [16][17][18][19][20][21][22][23] and PM ≤ 10 µm (PM10) [19,[22][23][24][25][26][27]), NO 2 [22,23] and O 3 [28].…”
Section: Introductionmentioning
confidence: 99%
“…Here only one event is of interest to the researcher, however, when considering another effect such as death due to other risks factors in the isolation center, then this is referred to as survival data with multiple events or simply competing risks [2]. In another word, when other events prevent the occurrence of events of interest, then, we say competing events (risk) exist [3]. Researchers such [4], [5], [6], and so on have applied the classical concept of analyzing survival data in the realm of nonparametric and semiparametric methods.…”
Section: Introductionmentioning
confidence: 99%